How can firms in the UK alcoholic drinks manufacturing sector improve their implementation of CSR? - Gee, Stephen Mark (2005)
The question of how firms in the UK alcoholic drinks manufacturing sector can improve their implementation of CSR is addressed. The structure of the industry, its products, trends and modes of distribution are first analysed and the leading manufacturers identified. The non-market environment is analysed in detail using Baron's framework (Baron 1995) in particular the industry issues and stakeholders are identified; the expectations of each of these stakeholders are then investigated. Using these stakeholder expectations the Corporate Social Performance of each firm is then assessed using Wood and Jones' measurement methodology (Wood and Jones 1995). The areas where firms' responses to stakeholder expectations are found to be weak are: extending their influence down the supply chain to persuade retailers to fulfill their obligations; warning the public of the consequences of excessive consumption and providing a financial contribution towards tackling the harm caused by excessive drinking. The literature on the implementation of CSR is reviewed; this review formed the basis of in-depth interviews with representatives from a number of alcoholic drinks manufacturing firms. The analyses of these interviews are presented and discussed in order to establish how each firm currently implements their CSR strategies within their organizations. The findings are related back to the ideas and theory identified in the literature review which allows recommendations to be made as to how to improve on the current levels of implementation. Furthermore, theory was developed during the course of the study identifying key factors associated with improving CSR implementation. The study concludes that there is a clear correlation between more advanced levels of implementation and better levels of CSP. It also concludes that present implementation strategies can only achieve limited social performance and that strategies need to be further developed to make organizational learning the main target for all firms trying to improve. Key elements contributing to the organizational learning process are found to be, first and foremost, the commitment of the firm's executives to achieving learning. Firms also need to encourage and empower their employees to act as stewards for the organization; communication processes play a key role in this. To improve learning a balance must also be struck between firms allowing experimentation within the organization and focusing on outcomes of strategies, which few do at present.